EDUKASI SANITASI DIRI UPAYA PENCEGAHAN PENYAKIT KULIT PADA SISWA SMA TAHFIDZ QUR’AN AMANAH KAB. DELI SERDANG - Harahap, Nina Irmayanti; Sianipar, Masria Phetheresia; Sembiring, Pintata (INSTITUT KESEHATAN DELI HUSADA, 2024)
The role of pharmacists is very important in helping people change their living habits to maintain good personal sanitation. Inadequate personal sanitation and a lack of awareness of maintaining personal sanitation are at great risk of being affected by skin diseases. The impact of skin diseases encourages people to self-medicate using medicines that are easily available and cannot be separated from the risk of inappropriate and rational use of medicines. The aim of this community service activity is to increase the knowledge and awareness of Tahfidz Qur'an Amanah District High School students. Deli Serdang in maintaining personal sanitation as an effort to prevent skin diseases so that it can increase awareness and change students' mindsets about self-sanitation. This community service activity is carried out using a consultative outreach method in providing education about personal sanitation. Education is provided through lectures, discussions, questions and answers and demonstrations about personal sanitation. The results of this service activity show an increase in knowledge about self- sanitation among Tahfidz Amanah High School students after being given education. Conclusion: This community service activity was carried out in the direction expected. Pharmacists play an important role in helping students change their mindset and increase awareness about personal sanitation. This is demonstrated by the increasing understanding of Tahfidz Amanah High School students regarding self-sanitization to prevent skin diseases based on eval_uation results after education on self-sanitation to prevent skin diseases.